2021
DOI: 10.1097/bpo.0000000000001853
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Proximal Tibial Metaphyseal Width and Lateral Epiphyseal Height Improves Determination of Remaining Growth in Children

Abstract: Background: Accurate assessments of skeletal maturity is of critical importance to guide type and timing of orthopaedic surgical interventions. Several quantitative markers of the proximal tibia were recently developed using historical knee radiographs. The purpose of the present study was to determine which marker would be most effective in assessment of fulllength radiographs in a modern pediatric patient population. Methods: All full-length radiographs at our institutions between 2013 and 2018 were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…We also utilized the first post-treatment radiographs performed within 2 weeks of surgery which provided more standardized imaging on which to perform our skeletal maturity assessments. Third, the Kahan formula utilized in this study to estimate GRP was derived from the Bolton Brush study, which was sourced in 1926 from predominantly white children from wealthy families 13,16 . As such, while prior studies have demonstrated the Brush cohort has matched well to a modern cohort, it is possible that this influences generalizability in our predominantly Black and more socioeconomically diverse cohort 11 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We also utilized the first post-treatment radiographs performed within 2 weeks of surgery which provided more standardized imaging on which to perform our skeletal maturity assessments. Third, the Kahan formula utilized in this study to estimate GRP was derived from the Bolton Brush study, which was sourced in 1926 from predominantly white children from wealthy families 13,16 . As such, while prior studies have demonstrated the Brush cohort has matched well to a modern cohort, it is possible that this influences generalizability in our predominantly Black and more socioeconomically diverse cohort 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Two maturity markers capable of being generated exclusively from knee radiographs were identified. Kahan and colleagues developed a system for predicting skeletal maturity based on measurements of the regional physes of the knee which was derived from a study cohort of primarily adolescents 13,16–19 . Their growth remaining percentage (GRP) was calculated using the following formula:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations